Optimization of allosteric MEK inhibitors. Part 2: Taming the sulfamide group balances compound distribution properties. Issue 1 (1st January 2016) - Hartung, Ingo V.; Hammer, Stefanie; Hitchcock, Marion; Neuhaus, Roland; Scholz, Arne; Siemeister, Gerhard; Bohlmann, Rolf; Hillig, Roman C.; Pühler, Florian
Graphical abstract: Abstract: Recently, we had identified an unexplored pocket adjacent to the known binding site of allosteric MEK inhibitors which allowed us to design highly potent and in vivo efficacious novel inhibitors. We now report that our initial preclinical candidate, featuring a phenoxy side chain with a sulfamide capping group, displayed human carbonic anhydrase off-target activity and species-dependent blood cell accumulation, which prevented us from advancing this candidate further. Since this sulfamide MEK inhibitor displayed an exceptionally favorable PK profile with low brain penetration potential despite being highly oral bioavailable, we elected to keep the sulfamide capping group intact while taming its unwanted off-target activity by optimizing the structural surroundings. Introduction of a neighboring fluorine atom or installation of a methylene linker reduced hCA potency sufficiently, at the cost of MEK target potency. Switching to a higher fluorinated central core reinstated high MEK potency, leading to two new preclinical candidates with long half-lives, high bioavailabilities, low brain penetration potential and convincing efficacy in a K-Ras-mutated A549 xenograft model.